TRANSFORMATION OF PROPHETIC COMMUNICATION PATTERNS IN THE ERA OF ARTIFICIAL INTELLIGENCE: CHALLENGES AND OPPORTUNITIES FOR ISLAMIC PREACHING IN INDONESIA - Ridwan, Aang; Rustandi, Ridwan (Fakultas Ushuluddin dan Dakwah UIN Raden Mas Said Surakarta, 2025)
principles to algorithm-based religious content. Despite the contradiction between the comprehensive nature of Islamic da’wah (kāffah) and fragmented digital da’wah practices, there is no adequate theoretical framework to bridge the transformation of religious authority when algorithms modify da’wah messages without supervision. The study examines changes in Islamic da’wah practices in the digital era, utilizing artificial intelligence, and employs a qualitative descriptive-analytical approach. The results reveal seven significant impacts: 1) a shift from spiritual-moral aspects to technology-driven message dissemination; 2) format adaptation following digital trends; 3) social media's influence in expanding access; 4) artificial intelligence contributions in content presentation; 5) challenges in balancing popularity with teaching integrity; 6) ethical issues in religious communication; and 7) the importance of education and supervision. The findings have significant implications for Islamic educational institutions, suggesting an urgent need to develop integrated curricula that equip future religious leaders with both technological competencies and an understanding of prophetic communication ethics in digital contexts, thereby maintaining the integrity of Islamic teachings while engaging contemporary audiences.